Budgeting in Kazakhstan A roadmap for continued budgetary governance reform - Beazley, Ivor (OECD Publishing, 2019)
The Republic of Kazakhstan is the largest economy in central Asia, and one of the fastest growing in the region. Having benefited from oil wealth as well as a diversifying and liberalised economy, Kazakhstan envisages a progressive modernisation of the political, administrative and juridical culture within the country. While strong progress has already been made on several fronts, other aspects of these envisaged reforms are at early stages. This OECD review takes stock of these reform efforts, and is designed to assist the national authorities in charting a course for future reforms and innovations
Keywords: Governance; Kazakhstan